Hubungan Loneliness dengan Parasocial Relationship pada Dewasa Awal Penggemar NCT di Sumatera Barat - Alifia Putri Fadilah Sati; Zulian Fikry (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze the relationship between Loneliness and Parasocial Relationships among Early Adult NCT Fans in West Sumatra. This study used a quantitative method involving 387 early adult NCT fans in West Sumatra. The instrument used for the Loneliness variable in this study was the De Jong Gierveld Loneliness Scale (DJGLS) developed by De Jong Gierveld and Kamphuis (1985) based on Weiss's (1973) loneliness theory and adapted into Indonesian by Triwahyuni, Agustiani, Hinduan, and Ruiter (2025). Meanwhile, for the Parasocial Relationship variable, a scale developed by the researcher based on Tukachinsky's (2010) theory was used. The results of the analysis showed a significant positive correlation between Loneliness and Parasocial Relationships (r = 0.339), with a significance value of 0.001 (p < 0.05). This finding indicates that the higher the Loneliness, the higher the Parasocial Relationship experienced by early adult NCT fans in West Sumatra. Likewise, the higher the Parasocial Relationship, the greater the Loneliness experienced by young adult NCT fans in West Sumatra.